Simulation of absorption spectrum of photosynthetic pigments of chlorella vulgaris B algae - Mahmoud Ahmed, Gharib Subhi; Hassan, Taher; Othman, Rashidi; Messikh Azeddine, Azeddine (Institute for Mathematical Research (INSPEM), Universiti Putra Malaysia, 2016)
Absorption spectrum of Chlorella vulgaris B algae was reconstructed by simulated the absorption spectrum of the mixture under examination by a linear combination of the absorption spectra of all its constituents. A C30 reversed high performance liquid chromatography equipped with photodiode array detector (HPLC-PAD) and absorption spectrophotometer were used to separate and identify photosynthetic pigments of Chlorella vulgaris B. Spectrum-reconstruction method (SRCM) was used to calculate concentrations of total carotenoids, chlorophylls a and b. Absorption spectrum of the total pigments extracted of Chlorella vulgaris B. was reconstructed from the sum of the spectrum of individual extracted pigments taken from (HPLC-PAD), and compared using normalization with absorption spectrum of the total pigments recorded by spectrophotometer. A total of seven Pigments were separated and identified